Case Report: Safety and Efficacy of Enfortumab Vedotin in a Patient With Metastatic Urothelial Carcinoma Undergoing Peritoneal Dialysis - Collette, Kaylyn R.; Myint, Zin W.; Parasramka, Saurabh V.; Ellis, Carleton S. (Frontiers in Oncology, 2022)
The clinical management of metastatic urothelial carcinoma has significantly evolved with the emergence of monoclonal antibodies and antibody-drug conjugates (ADCs). Enfortumab vedotin (EV) was granted approval by the FDA in 2021 for patients with locally advanced or metastatic urothelial carcinoma who have received prior immunotherapy and platinum-containing chemotherapy. Little to no data exists for the use of EV in patients with concurrent end-stage renal disease (ESRD) utilizing either hemodialysis or peritoneal dialysis (PD). Here, we present the case of a patient with metastatic urothelial carcinoma on PD who failed multiple lines of treatment but demonstrated an impressive response to EV without significant toxicity. We discuss the possible impact of peritoneal dialysis on the pharmacokinetics of ADCs and the potential for safe administration based on known pharmacokinetic data.